Development of Teaching Model Mobile Seamless Learning as Future Teaching Guide - Najibulmuti’e Hamdan, Muhammad; Ghazali, Norliza; Mustakim, Siti Salina (Journal of Public Administration and Governance, 2023)
The effective teaching and learning process in a class is one of the important aspects that need to be emphasized nowadays. There are various ways for teachers to plan teaching content in our education system. The development of mobile technology such as smart phones can help student learning happen outside of context, that is, it can happen regardless of time and place without being bound by space and time. This has the opportunity to create learning that occurs naturally. Students can be equipped with facilities so that they can go through the learning process without having to think about time constraints and where as long as it suits their wishes. Therefore, accurate teaching concepts and planning in preparation for effective learning for students are very necessary when using mobile technology. This is an innovative method where students are exposed to the outside world through technology. However, the implementation of this method is not as easy as expected if there is not enough support from teachers as teaching staff. The learning process that takes place without time and space limitations that contains the concepts of fluency and continuity is a teaching model known as Mobile Seamless Learning (MSL). This article explains the concept without limitations in developing teaching and learning based on MSL.